Research on the Problem and Solutions to Formation of Communication Skills (Eurasian Research Bulletin, 2023)
Our article discusses the problem of designing the communication space of students and future teachers as a means of improving pedagogical communication. The authors show approaches; You will get acquainted with the semantic accents to understand the communicative abilities and the conditions of their appearance